ANALISA KINERJA KA KOMUTER SURABAYA – LAMONGAN - Sugeng Dwi Hartantyo; Hammam Rofiqi Agustapraja (Kadiri University, 2018)
Commuter Rail Operation is prioritized for the middle to lower classes. But in fact the prospective commuter train passengers complained of comfort in this regard relating to the number of seats and standing places available. The discussion was analyzing the comfort per seat and standing that had been set, analyzing the operational capacity of the Surabaya - Lamongan Commuter Railway. To be able to answer these problems, a study was carried out on Commuter Trains and related agencies. From the analysis results obtained the value of comfort of the seat (r) = 0.4 m2 / space and the value of comfort of the stand (σ) = 0.87m2 / space. The total capacity of one series of commuter trains (Cv) is 312 passengers, while the total seating capacity for a series of commuter trains is 248 passengers. Average Load Factor (LF) of 0.51. Keywords: Commuter Trains, Performance, Capacity, Comfort Level Pengoperasian KA Komuter diutamakan bagi masyarakat kalangan menengah kebawah. Namun pada faktanya para calon penumpang kereta api komuter mengeluhkan kenyamanan dalam hal ini yang berkaitan dengan jumlah tempat duduk dan tempat berdiri yang tersedia.Pembahasan ini adalah menganalisa kenyamanan per tempat duduk dan berdiri yang telah ditetapkan, menganalisa kapasitas kendaraan operasional KA Komuter Surabaya – Lamongan, Untuk dapat menjawab permasalahan tersebut maka dilakukan penelitian terhadap KA Komuter dan instansi terkait. Dari hasil analisa didapatkan nilai kenyamanan tempat duduk (r) = 0,4 m2/space dan nilai kenyamanan tempat berdiri (σ) = 0,87m2/space. Kapasitas total satu rangkaian KA Komuter (Cv) sebesar 312 penumpang, sedangkan kapasitas total tempat duduk untuk satu rangkaian KA Komuter sebesar 248 penumpang. Rata-rata Load Factor (LF) sebesar 0,51. Kata Kunci : Kereta Komuter, Kinerja, Kapasitas, Tingkat Kenyamanan